A novel method of neptunium-237 detection in its separated form and advanced fuel based on photonuclear reactions. (1st June 2022) - Tanabe, Kosuke; Sagara, Hiroshi
Highlights: The photon-induced multiple neutron generation reaction rate ratio (PMNRR) method was proposed to detect 237 Np. A combination of photon energies ranging over 12–15 MeV and 6–11 MeV was selected. The feasibility of the detections of the separated 237 Np and the 237 Np above a certain composition ratio in UO2 was verified. The PMNRR method is robust to the energy distribution of incident photons. Abstract: This paper presents a novel method for the detection of 237 Np in its separated form and advanced fuel by applying the principle of the photofission reaction ratio (PFRR). In this method, 237 Np was identified using the photon-induced multiple neutron generation reaction rate ratio (PMNRR) with multiple high-energy gamma rays. The feasibility of the discrimination between the separated 237 Np and uranium ( 235 U, 238 U) and the detection of the 237 Np above a certain composition ratio in UO2 was examined by numerical analysis simulation. The proposed method has a wide range of incident photon energy selectivity because it utilizes the (*, 2n) reaction, which is considered an inevitable measurement obstacle in the PFRR method. The results show the detectability of 237 Np even with a 10% uncertainty in the nuclear data of the (γ, fission/2n) reaction, and the robustness of the PMNRR method to the energy distribution of incident photons. In the future, the proposed method is expected to be applied for detection and verification in the field of nuclear non-proliferation and security.